The development of the level of environmental awareness among the residents in cities and residential neighborhoods - Lamdjad, Imane; Alfalahi, Buti Obaid Saeed; Alnujaifi, Mustafa; Alheety, Noaman Atallah (Edelweiss Applied Science and Technology, 2024)
This research aims to develop and increase the level of environmental awareness regarding climate change and sustainability issues among individuals in cities and residential neighborhoods. The current research methodology is descriptive and analytical, based on a questionnaire tool consisting of (34) questionnaires. It was designed on the basis of (12) axes covering environmental awareness and environmental problems to obtain more accurate results. The research finds that there is a lack of environmental awareness among most individuals for many reasons, such as weak environmental culture and low educational level, in addition to a lack of interest in climate change issues. The research proposes several recommendations that are necessary to enhance the confidence of individuals and the population in technology, and promote environmental participation among all those concerned with environmental awareness, starting with decision-makers, politicians, government agencies, non-profit organizations, the private sector, and the population.